Strategic Communication in Agile Organizations: Why Does Agile Face Skepticism in Organizations? - Fóris, Ágota; Kerner, Robert P. (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2024)
Agile was initially developed as a methodology for software development, emphasizing iterative progress, flexibility, and collaboration. Over time, its principles have been adapted and applied to broader business operations and strategic communication processes. Like many business methodologies, Agile has its proponents who champion its benefits and skeptics who questionits effectiveness. This paper aims to identify the root cause of the skepticism surrounding Agile methods and to examine a case study that provides relevant insights and context. The data for this analysis was collected through direct observation by one of the authors at the largest university in the United States. The paper will investigate how and why communication during an Agiletransformation differs from other organizational transformations, focusing on the fundamental frameworks essential for supporting the Agile transformation and its communication strategies.The findings suggest that a critical factor in addressing skepticism toward Agile methods is the establishment of a well-defined foundation of terminology, which is key for fostering effective and efficient communication. In an Agile organization, awareness and understanding of terminology should be embedded in the organizational culture.